Osteocalcin, Vascular Calcification, and Atherosclerosis: A Systematic Review and Meta-analysis - Millar, Sophie A.; Patel, Hinal; Anderson, Susan I.; England, Timothy J.; O’Sullivan, Saoirse E. (Frontiers in Endocrinology, 2017)
Background: Osteocalcin is an intriguing hormone, concomitantly being the most abundant non-collagenous peptide found in the mineralised matrix of bone, and expanding the endocrine function of the skeleton with far-reaching extra-osseous effects. A new line of enquiry between osteocalcin and vascular calcification has emerged in response to observations that the mechanism of vascular calcification resembles that of bone mineralisation. To date, studies have reported mixed results. This systematic review and meta-analysis aimed to identify any association between osteocalcin and vascular calcification and atherosclerosis. Methods and results: Databases were searched for original, peer reviewed human studies. A total of 1453 articles were retrieved, of which 46 met the eligibility criteria. Overall 26 positive, 17 negative, and 29 neutral relationships were reported for assessments between osteocalcin (either concentration in blood, presence of osteocalcin positive cells, or histological staining for osteocalcin) and extent of calcification or atherosclerosis. Studies which measured osteocalcin positive cells or histological staining for osteocalcin reported positive relationships (11 studies). A higher percentage of Asian studies found a negative relationship (36%) in contrast to European studies (6%). Studies examining carboxylated and undercarboxylated forms of osteocalcin in the blood failed to report consistent results. The meta-analysis found no significant difference between osteocalcin concentration in the blood between patients with ‘atherosclerosis’ and control (p=0.13, n=1197). Conclusions: No definitive association was determined between osteocalcin and vascular calcification or atherosclerosis, however, the presence of osteocalcin positive cells and histological staining had a consistent positive correlation with calcification or atherosclerosis. The review highlighted several themes which may influence osteocalcin within differing populations leading to inconclusive results. Large, longitudinal studies are required to further current understanding of the clinical relevance of osteocalcin in vascular calcification and atherosclerosis.